Digitalisierung lokaler Medien Genese und Zukunft des nordrhein-westfälischen Zwei-Säulen-Modells im lokalen Rundfunk - Kalbhenn, Jan Christopher (Mohr Siebeck, 2024)
Large online platforms and social networks threaten local media diversity. In North Rhine-Westphalia, the globally unique two-pillar model ensures that every town has its own local radio station. But can this model survive in the digital age or is a change of system necessary? From a constitutional and broadcasting law perspective, the author discusses the benefits and disadvantages of state funding, stricter requirements for digital media platforms and an expansion of the mandate for public broadcasting in the local area.
PublicationDate: 20240228
Keywords: Social Media -- Unternehmerisches Ermessen -- Internet- und Plattformökonomie -- Schweigerecht -- lokale Medienvielfalt -- öffentlich-rechtlicher Rundfunk -- Lokaljournalismus -- Gnosis/Gnostizismus -- Spotify -- Drittbeteiligung -- Auffindbarkeit -- Improvement of the world -- Landesmediengesetz -- Verfassungsrecht und Staatslehre -- Besonderes Verwaltungsrecht -- Völkerrecht -- Europarecht